Oral condition of institutionalized older people: Influence on anthropometric indicators, food and nutrient intake - Galesi-Pacheco, Lilian Fernanda [UNESP]; Leandro-Merhi, Vania Aparecida; Azzolin, Gabriela Marchiori Carmo; de Oliveira, Maria Rita Marques [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2021)
Objective: To assess whether there are differences between oral problems and food, energy, and nutrient intake and anthro-pometric indicators of institutionalized older adults. Methods: A total of 150 older people participated in the study. Their nutritional status was determined by anthropometric indicators and food intake. Oral problems were examined by a trained dentist who checked for caries, periodontitis, dry mouth, edentulism, and poorly-fitting partial or complete dentures. The categorical variables were analyzed by the Fisher’s Exact Test and the continuous variables were analyzed by the Student’s t-test for parametric data and the Mann–Whitney test for nonparametric data (p≤0.05). Results: Older people with oral problems presented lower anthropometric measurements and indices except for biceps skinfold thickness and consumed less energy (p= 0.027), protein (p= 0.012), lipids (0.012), and pan-fried meats (p= 0.001). Conclusion: Anthropometric indicators and the energy, protein and lipid intake were lower in elderly people with oral problems. This work warns about the importance of oral health for the good nutrition of older people and the need to establish strategies to adapt the diet of this population.
Condición oral de las personas mayores institucionalizadas: Influencia en los indicadores antropométricos y la ingesta de alimentos y nutrientes
Keywords: Anthropometry; Food intake; Nutritional status; Older people nutrition; Oral health